A Social-Ecological Approach to Understanding Activity Engagement Patterns Among Older Chinese Immigrants. (March 2023) - Tang, Fengyan; Li, Ke; Rauktis, Mary E.; Chi, Iris; Dong, XinQi
Few studies have focused on activity engagement among older immigrants. We aim to map the patterns of activity engagement and examine the associations with social-ecological factors in a sample of older Chinese immigrants. Participants were from the Population Study of Chinese Elderly in Chicago (PINE). Four patterns of activity engagement were identified through latent class analysis: restricted, diverse, informal social, and community-based social. Intrapersonal, interpersonal, cultural, and environmental factors distinguished latent classes of activity engagement. In particular, acculturation and family-oriented immigration differentiated the restricted from the diverse class membership. Positive attributes of social environment such as social network size, positive social support, and neighborhood cohesion were associated with the likelihood of categorization in the diverse, informal social, and community-based social groups relative to the restricted group. Findings point to the importance of positive attributes of social environment in enhancing engagement with life among older Chinese immigrants.